2020
DOI: 10.3390/ijms21051834
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Antitumor Immunity by Exosomes Isolated from Cryopreserved Cord Blood Monocyte-Derived Dendritic Cells

Abstract: (1) Background: Dendritic cell (DC) vaccination has shown outstanding achievements in cancer treatment, although it still has some adverse side effects. Vaccination with DC-derived exosomes has been thought to overcome the side effects of the parental DCs. (2) Method: We performed the experiments to check the ability of cryopreserved umbilical cord blood mononuclear cell-derived DCs (cryo CBMDCs) and their exosomes to prime allogeneic T cell proliferation and allogeneic peripheral blood mononuclear cell (alloP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…These results were consistent with the study of Nidea et al (2015), which reported that highly expressing CD56 IFN-DCs induced the proliferation and activation of Vγ9TCR T cells in vitro and in vivo better than conventional IL-4DCs. 22 In a recent published study of our research group, 34 we also generated IL-4DCs from cord blood monocytes and the proliferation of Vγ9γδ T cells stimulated with these IL-4DCs are smaller than that stimulated by IFN-DCs in this current study.…”
Section: Discussionmentioning
confidence: 49%
“…These results were consistent with the study of Nidea et al (2015), which reported that highly expressing CD56 IFN-DCs induced the proliferation and activation of Vγ9TCR T cells in vitro and in vivo better than conventional IL-4DCs. 22 In a recent published study of our research group, 34 we also generated IL-4DCs from cord blood monocytes and the proliferation of Vγ9γδ T cells stimulated with these IL-4DCs are smaller than that stimulated by IFN-DCs in this current study.…”
Section: Discussionmentioning
confidence: 49%
“…The unique characteristics of exosomes and their ability to carry cargo to distant destinations in the body makes them ideal candidates to signal between feto-maternal tissues during pregnancy [15]. Studying the contribution of exosomes in pathological pregnancies and related diseases, such as infertility or pregnancy failure can open the way for new exosome-based therapies [118].…”
Section: Resultsmentioning
confidence: 99%
“…Monocytes isolated from cryopreserved CB could be potentially transplanted for treating inherited demyelinating conditions of the central nervous system [ 23 ]. Additionally, dendritic cells derived from cryopreserved CB monocytes were observed to exhibit antitumor potential [ 24 ]. Induced pluripotent stem cells were generated from HSCs isolated from 21- to 23.5-year-old cryopreserved CB samples that showed optimal storage recovery of HSCs for future clinical utility [ 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%